Digitalization of the Development of the Daily Stock Implementation System for the Logistics Section at Rsud Should Obey Patju - Wahidah, Baiq; Darmawan, Cecep; Rinawati, Rinawati (Journal of Economics and Social Sciences (JESS), 2025)
This study aims to find out the current daily stock recording process, identify the obstacles faced, and formulate a development strategy to increase the effectiveness of the daily stock recording system in the logistics section of the Patut Patuh Patju Hospital. The research method uses a descriptive qualitative approach through in-depth interviews with logistics managers, warehouse heads, and logistics staff, as well as direct observation and documentation related to the flow of daily stock recording and management. The results of the study show that the daily stock recording process is still carried out manually using stock cards, Excel programs, and supporting documents. This process runs systematically starting from the procurement of goods, receipt, to distribution to service units, but still faces obstacles in the form of mismatches between records and physical conditions in the warehouse, delays in reporting, and the risk of errors due to negligence in recording and managing amprahan documents. This condition creates a high administrative burden and reduces efficiency, especially when reporting at the end of the month. The proposed development strategy includes the implementation of a digital-based recording system integrated with hospital information systems, increasing the capacity of human resources through technical training, and rearranging coordination procedures between units to make logistics flows more efficient, transparent, and accurate. The implementation of this strategy is expected to strengthen inventory control and support the improvement of hospital service quality.